Survival Strategy of Rainfed Farmers in Koanyar Village, Klabang Bondowoso - Murtiah, Murtiah; Mulyono, Joko (Laboratorium Sosiologi FISIP Universitas Jember, 2019)
This research is a qualitative descriptive study that aims to describe and analyze the survival strategies of rainfed farmers in the Koanyar sub-village, Klabang Bondowoso. Rainfed lowland rice farming in Koanyar Hamlet is caused by a lack of water supply, which affects dry and dead plants. Ownership of rain-fed rice fields causes farmers only to be able to plant once a year, which results in low farmer income. Therefore, farmers make various ways to survive in stressful situations. Researchers use James C. Scott's frame of mind about Survive Mechanisms. The results showed that rainfed farmers survive by saving, working side by side, maintaining good relations with patrons and increasing the ability to grow crops using a water-sucking machine, and selecting plants according to the season. Keywords: Rainfed lowland, Low-income farmers, Survival Strategies Referensi: Afrizal. 2014. Metode Penelitian Kualitatif: Sebuah Upaya Penggunaan Penelitian Kualitatif Dalam Berbagai Disiplin Ilmu. Jakarta: Rajawali Pers. Bungin, Burhan. 2007. Metodologi Penelitian Kualitatif. Jakarta: PT Raja Grafindo. —. 2006. Sosiologi Komunikasi: Teori, Paradigma, dan Diskursus Teknologi Komunikasi di Masyarakat. Jakarta: KENCANA. Creswell. 2010. Research Design: Pendekatan Kualitatif, Kuantitatif, dan Mixed. Yogyakarta: Pustaka Belajar. Jacky. 2015. Sosiologi Konsep, Teori, dan Metode. Jakarta: Mitra Wacana Media. Mansyur. 2005. Sosiologi Masyarakat Kota & Desa. Surabaya: Usaha Nasional. Martono, Nanang. 2012. Sosiologi Perubahan Sosial: Perspektif Klasik, Modern, Posmodern, dan Poskolonial. Jakarta: Rajawali Pers. Narwoko, J. Dwi dan Bagong Suyanto. 2011. Sosiologi: Teks Pengantar dan Terapan, Edisi Keempat. Jakarta: Kencana Prenada Media Group. Resmi, Setia. (2005). Gali Tutup Lubang Itu Biasa: Strategi Buruh Menanggulangi Persoalan dari Waktu ke Waktu. Bandung: Yayasan Akatiga. Salim, Emil. 1986. Pembangunan Berwawasan Lingkungan. Jakarta: LP3ES. Scott, James. 1981. Moral Ekonomi Petani. Jakarta: LP3ES. Sugiyono. 2008. Metode Penelitian Kuantitatif, Kualitatif dan R & D. Bandung: Alfabeta. Suryabrata, Sumardi. 2008. Metodologi Penelitian. Jakarta: PT Raja Grafindo Persada. Syahyuti. 2006. 30 Konsep Penting dalam Pembangunan Pedesaan dan Pertanian: Penjelasan tentang